The Use of Chromium and Chromium (III) Oxide PVD Coatings to Resist the Corrosion Driven Coating Delamination of Organically Coated Packaging Steel - Natalie Wint (Journal of The Electrochemical Society, 2020)
This paper describes a systematic study into the role of chromium and chromium (III) oxide thickness in preventing corrosion driven coating disbondment of organically coated packaging steel. A graded wedge of chromium and chromium (III) oxide is applied to steel using physical vapour deposition (PVD). A polyvinyl butyral (PVB) overcoat is applied and corrosion is initiated from an artificial defect using NaCl. Scanning Kelvin probe (SKP) potentiometry is used to monitor coating delamination. Wedge thickness variation allows for high throughput investigations into the effect of both metallic chromium and chromium (III) oxide thickness, on coating disbondment rate. A linear reciprocal relationship is observed between chromium metal thickness and disbondment rate. Increasing chromium (III) oxide thickness (applied over chromium metal) results in a decrease in delamination rate. This work highlights the ability of PVD to produce chromium/chromium (III) oxide corrosion resistant coatings to use as alternatives to hexavalent chromium-based systems.